Adverse Pregnancy Outcomes of Patients with History of First-Trimester Recurrent Spontaneous Abortion - Yang, Jing (Biomed Res Int, 2017)
Although a history of first-trimester recurrent spontaneous abortion (FRSA) is regarded as a risk factor in antenatal care, the characteristic of subsequent pregnancy outcome is not clearly elucidated. Here, a retrospective analysis was performed on the clinical data of 492 singleton pregnant women. 164 of them with the history of FRSA were enrolled in study group, compared to 328 deliveries without the history of FRSA. For maternal outcomes, patients in the study group delivered earlier with mean gestational age and the incidences of cesarean section and postpartum hemorrhage were higher compared to the control group. For placental outcomes, the incidence of placenta-mediated pregnancy complications (PMPC) in the study group increased in terms of late-onset preeclampsia, oligohydramnios, early-onset fetal growth restriction, and second-trimester abortion. Patients in the study group were more likely to suffer from placenta accreta, placenta increta, and placenta percreta. For perinatal outcomes, the proportion of birth defects of newborns in the study group was greater. At last, logistic regression analyses showed that the history of FRSA was an independent risk factor for cesarean section and pregnancy complications. In conclusion, women with the history of FRSA are often exposed to an elevated incidence of maternal-placental-perinatal adverse pregnancy outcomes.